Rice Quality and Yield at Various Application Times of Organic Rice Management System - Jauhari Syamsiyah; Dwi Priyo Ariyanto; Aktavia Herawati; Komariah Komariah; Sri Hartati; Fitri Nurbaiti (UNIVERSITY OF LAMPUNG, 2023)
The higher national rice demand encourages various efforts to increase rice production. This increase in rice production occurs in line with increasing public awareness of healthy foods, especially organic rice. Rice field management with an organic system is expected to provide a higher yield and quality of rice. This study aims to determine the effect of the long-time application of an organic rice management system on rice yield and quality. Descriptive exploratory research is supported by laboratory analysis of samples of organic rice plants with three periods (10 years, 7 years, and 4 years), semi-organic and conventional. The parameters observed were dry harvested grain, dry milled grain, the weight of 1000 grains, unfilled grain, protein content, amylum, amylopectin, and reducing sugar. The most prolonged organic rice field management with the application of 10 years gives better results with a protein content of 6.14%, amylum 71.71%, and amylopectin 49.35%. While the application of organic farming for 7 years gives the highest rice yield, the difference is not confirmed with the application of organic 10 years, with the weight of dry grain harvest 10.44 Mg ha-1, dry milled grain 8.15 10.44 Mg ha-1, the weight of 1000 grains 24 g, and unfilled grain 3.8%.